Food-dependent, exercise-induced gastrointestinal distress - de Oliveira, Erick Prado [UNESP]; Burini, Roberto Carlos [UNESP] (Biomed Central Ltd., 2011)
Among athletes strenuous exercise, dehydration and gastric emptying (GE) delay are the main causes of gastrointestinal (GI) complaints, whereas gut ischemia is the main cause of their nausea, vomiting, abdominal pain and (blood) diarrhea. Additionally any factor that limits sweat evaporation, such as a hot and humid environment and/or body dehydration, has profound effects on muscle glycogen depletion and risk for heat illness. A serious underperfusion of the gut often leads to mucosal damage and enhanced permeability so as to hide blood loss, microbiota invasion (or endotoxemia) and food-born allergen absorption (with anaphylaxis). The goal of exercise rehydration is to intake more fluid orally than what is being lost in sweat. Sports drinks provide the addition of sodium and carbohydrates to assist with intestinal absorption of water and muscle-glycogen replenishment, respectively. However GE is proportionally slowed by carbohydrate-rich (hyperosmolar) solutions. on the other hand, in order to prevent hyponatremia, avoiding overhydration is recommended. Caregiver's responsibility would be to inform athletes about potential dangers of drinking too much water and also advise them to refrain from using hypertonic fluid replacements.
Keywords: diet; gastrointestinal distress; physical exercise